A novel technique for spreader graft placement without dorsum resection during septoplasty. Issue 10 (October 2015) - Kaya, E; Catli, T; Soken, H; Cingi, C
Abstract Objective: This paper presents a novel method for spreader graft placement without dorsum resection in patients who have a deviated septum with a narrow internal nasal valve angle. Methods: A Killian incision was used for the endonasal septoplasty, and all spreader grafts were harvested from excised deviated septal cartilages. Procedures were conducted under general anaesthesia at the same centre by the same surgical team that performed the endonasal procedure. Successful placement of spreader grafts was achieved endonasally. Conclusion: Although the endonasal placement of spreader grafts seems to be more difficult than placement conducted by an open approach technique, an endonasal procedure has many advantages. Our technique provides surgeons with the opportunity to shorten operation time, obtain autologous septal graft material and secure the columellar architecture. Surgeons familiar with the classical (endonasal) septoplasty procedure can easily apply this technique to widen a narrow internal nasal valve angle, without corrupting nasal integrity.